A disembodied man: A case of somatopsychic depersonalization in schizotypal disorder. Issue 4 (16th November 2015) - Zaytseva, Yuliya; Szymanski, Caroline; Gutyrchik, Evgeny; Pechenkova, Ekaterina; Vlasova, Rosa; Wittmann, Marc
Abstract: In the general concept of self‐disturbances in schizophrenia and schizophrenia spectrum disorders, somatopsychic depersonalization (SPD) occupies a special place as it constitutes a syndrome that comprises feelings of detachment from one's own body and mental processes. However, apart from clinical descriptions, to date the pathophysiology of SPD is not fully understood due to the rareness of the syndrome and a lack of experimental studies. In a case study of one patient with schizotypal disorder, we applied a multimodal approach to understanding the SPD phenomena. The patient's clinical profile was identified as disruption of implicit bodily function, accompanied by depressive symptoms. On a neuropsychological level, the patient exhibited impairment in executive functioning, intact tactile perception and kinesthetic praxis. Behavioral tests revealed an altered sense of time but unimpaired self‐agency. Furthermore, the patient exhibited a lack of empathy and he had autistic traits, although with a sufficient ability to verbalize his feelings. On the neurobiological level using an active and passive touch paradigm during functional magnetic resonance imaging (fMRI), we found a hyperconnectivity of the default‐mode network and salience network and a hypoconnectivity of the central executive brain networks in the performance of the touch task as well as intact perceptual touch processing emerging from the direct comparisons of the touch conditions. Our data provide evidence for the important role of altered large‐brain network functioning in SPD that corresponds to the specific behavioral and neurocognitive phenomena.